Perovskite solar cell and preparation method thereof, photovoltaic module
Patent Information
- Application Number
- CN202611186415.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-09-29
AI Technical Summary
本申请提供了一种钙钛矿太阳能电池及其制备方法、光伏组件,其中钙钛矿太阳能电池中的复合钝化层包括层叠的第一钝化子层、第二钝化子层和第三钝化子层,其中,第一钝化子层中含有第一钝化材料,所述第一钝化材料为分子量不大于300的离子型化合物,该离子型化合物含有氨基、脒基、氟基团和硫氰酸根中的至少一种,分子尺寸小、渗透能力强,能够深入钙钛矿层的晶界并重构钙钛矿层与电子传输层之间的界面,还能够钝化钙钛矿层中未配位Pb2+以及卤素缺陷;第二钝化子层中含有第二钝化材料,所述第二钝化材料为有机碘化物,能够诱导能带弯曲实现场效应钝化,同时形成致密物理屏障,不仅能够抑制钙钛矿层中钙钛矿材料的离子迁移,还能够阻挡水氧侵入钙钛矿层;第三钝化子层中含有第三钝化材料,所述第三钝化材料为n型电子受体材料,一方面,能够与第二子层的Ruddlesden-Popper(RP)二维相表面形成氢键、静电作用与配位键等特异性相互作用,另一方面,第三钝化子层是一种有序的二维功能层,能够精准调控钙钛矿层与电子传输层之间界面的偶极与能级对齐,强化该界面疏水阻隔能力,优化电子提取动力学,同时稳固复合钝化层的多层界面结构,抑制离子迁移与环境诱导的界面退化。本申请通过复合钝化层特有的三层结构以及材料的协同作用,实现钙钛矿叠层太阳能电池界面电荷输运与长期稳定性的协同提升。
Smart Images

Figure CN122846928A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of perovskite solar cells, and more particularly to a perovskite solar cell and its fabrication method, as well as a photovoltaic module. Background Technology
[0002] Perovskite tandem solar cells can further improve the utilization of the solar spectrum, thereby increasing the photoelectric conversion efficiency of solar cells.
[0003] In perovskite tandem solar cells, the passivation layer is a functional film layer located between the perovskite layer and the electron transport layer, serving to passivate the interface. How to improve the passivation layer to further enhance the performance of perovskite tandem solar cells has become a pressing technical problem to be solved. Summary of the Invention
[0004] To address the aforementioned technical problems, this application discloses a perovskite solar cell and its fabrication method, as well as a photovoltaic module, to improve the passivation capability of the passivation layer, thereby enhancing the performance of the perovskite tandem solar cell.
[0005] In a first aspect, this application provides a perovskite solar cell, comprising: The substrate and the hole transport layer, perovskite layer, composite passivation layer and electron transport layer are sequentially stacked on the substrate; The composite passivation layer includes a first passivation sublayer, a second passivation sublayer, and a third passivation sublayer stacked together. The first passivation sublayer is in contact with the perovskite layer, and the third passivation sublayer is in contact with the electron transport layer. The first passivation sublayer contains a first passivation material, which is an ionic compound with a molecular weight of no more than 300, and the ionic compound contains at least one of amino, amidine, fluorine and thiocyanate groups. The second passivation sublayer contains a second passivation material, which is an organic iodide; The third passivation sublayer contains a third passivation material, which is an n-type electron acceptor material.
[0006] In some embodiments of this application, the thickness of the first passivation sublayer is less than the thickness of the second passivation sublayer, and the thickness of the third passivation sublayer is less than the thickness of the second passivation sublayer.
[0007] In some embodiments of this application, the composite passivation layer satisfies at least one of the following characteristics: a) The thickness of the first passivation sublayer is 0.4 nm to 1.5 nm; b) The thickness of the second passivation sublayer is 2 nm to 2.6 nm; c) The thickness of the third passivation sublayer is 0.6 nm to 1.5 nm.
[0008] In some embodiments of this application, the ionic compound is selected from at least one of 1-[4-(trifluoromethyl)phenyl]biguanide hydrochloride, 1-phenylbiguanide hydrochloride, 4-(trifluoromethyl)benzamide hydrochloride, ammonium thiocyanate, and 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride.
[0009] In some embodiments of this application, the organic iodide is selected from at least one of 1,3-diaminopropane dihydroiodate, ethylenediamine dihydroiodate, malondiamidinium diiodate, 2-(4-fluorophenyl)ethylamine hydroiodate, straight-chain alkyl diammonium iodide, alicyclic diammonium iodide, aromatic diammonium iodide, fluorodiammonium hydroiodate, amidine iodide, and monocationic aralkylammonium iodide.
[0010] In some embodiments of this application, the linear alkyl diammonium iodide is selected from at least one of 1,4-butanediammonium dihydroiodate, 1,3-propanediammonium dihydroiodate, and 1,6-hexammonium dihydroiodate; The alicyclic diammonium iodide is selected from at least one of 1,2-cyclohexanediammonium dihydroiodate and piperazine diammonium dihydroiodate; The aromatic diammonium iodide is selected from at least one of o-phenyl diammonium dihydroiodate and biphenyl diammonium dihydroiodate; The fluorodiammonium hydroiodate is selected from at least one of tetrafluoroethylenediammonium dihydroiodate and tetrafluorophenyldiammonium dihydroiodate; The amidine-based iodides are selected from benzamide iodides; The monocationic aralkylammonium iodide is selected from at least one of phenylethylammonium iodide and fluorophenylethylammonium iodide.
[0011] In some embodiments of this application, the n-type electron acceptor material is selected from at least one of p-trifluoromethylbenzonitrile, p-fluorobenzonitrile, and pentafluorobenzoic acid.
[0012] In some embodiments of this application, the material of the electron transport layer includes C. 60 Fullerene C 70 At least one of (6,6)-phenyl-C61-butyrate methyl ester (PCBM) and 4-(1',5'-dihydro-1'-methyl-2'H-(5,6)fullerene-C60-In-(1,9-c)pyrrole-2'-yl)benzamine chloride (CPMAC).
[0013] Secondly, this application provides a method for fabricating a perovskite solar cell as described in the first aspect, comprising the following steps: A substrate is provided, the substrate comprising a bottom cell and a composite layer; A hole transport layer and a perovskite layer are sequentially prepared on the surface of the composite layer. The first passivation sublayer, the second passivation sublayer, and the third passivation sublayer are sequentially prepared on the surface of the perovskite layer to form the composite passivation layer; Other functional layers are sequentially prepared on the surface of the composite passivation layer, and the other functional layers include at least the electron transport layer.
[0014] Thirdly, this application provides a photovoltaic module comprising: at least one battery string, the battery string comprising at least two perovskite solar cells as described in the first aspect.
[0015] Compared with the prior art, this application has at least the following beneficial effects: This application provides a perovskite solar cell and its fabrication method, as well as a photovoltaic module. The composite passivation layer in the perovskite solar cell includes a stacked first passivation sublayer, a second passivation sublayer, and a third passivation sublayer. The first passivation sublayer contains a first passivation material, which is an ionic compound with a molecular weight not exceeding 300. This ionic compound contains at least one of amino, amidine, fluorine, and thiocyanate groups. It has a small molecular size and strong penetration ability, enabling it to penetrate deep into the grain boundaries of the perovskite layer and reconstruct the interface between the perovskite layer and the electron transport layer. It can also passivate uncoordinated Pb in the perovskite layer. 2+ The second passivation sublayer contains a second passivation material, which is an organic iodide. This material can induce band bending to achieve field-effect passivation and form a dense physical barrier. This barrier not only inhibits ion migration of the perovskite material in the perovskite layer but also prevents water and oxygen from penetrating the perovskite layer. The third passivation sublayer contains a third passivation material, which is an n-type electron acceptor material. On the one hand, it can form specific interactions such as hydrogen bonds, electrostatic interactions, and coordination bonds with the Ruddlesden-Popper (RP) two-dimensional phase surface of the second sublayer. On the other hand, the third passivation sublayer is an ordered two-dimensional functional layer that can precisely control the dipole and energy level alignment of the interface between the perovskite layer and the electron transport layer, strengthen the hydrophobic barrier ability of the interface, optimize electron extraction kinetics, and stabilize the multi-layer interface structure of the composite passivation layer, inhibiting ion migration and environment-induced interface degradation. This application achieves a synergistic improvement in interface charge transport and long-term stability of perovskite tandem solar cells through the unique three-layer structure of the composite passivation layer and the synergistic effect of the materials. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a schematic diagram of the structure of a solar cell in one embodiment of this application; Figure 2 This is a schematic diagram of the passivation layer, perovskite layer, and electron transport layer in one embodiment of this application; Figure 3 This is a schematic diagram of the structure of a solar cell in another embodiment of this application.
[0018] Explanation of reference numerals in the attached figures: 1-substrate, 2-hole transport layer, 3-perovskite layer, 4-composite passivation layer, 5-electron transport layer, 6-buffer layer, 7-first transparent electrode layer, 8-antireflection layer, 10-bottom cell, 11-second transparent electrode layer, 12-p-type window layer, 13-first intrinsic hydrogenated amorphous silicon passivation layer, 14-n-type silicon substrate, 15-second intrinsic hydrogenated amorphous silicon passivation layer, 16-n-type window layer, 17-composite layer, 21-transition metal oxide layer, 22-self-assembled monolayer, 41-first passivation sublayer, 42-second passivation sublayer, 43-third passivation sublayer, 91-positive electrode, 92-back electrode. Detailed Implementation
[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0020] In this application, the terms "upper," "lower," "left," "right," "front," "rear," "top," "bottom," "inner," "outer," "vertical," "horizontal," "lateral," and "longitudinal" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. These terms are primarily for the purpose of better describing this application and its embodiments, and are not intended to limit the indicated device, element, or component to having a specific orientation, or to be constructed and operated in a specific orientation.
[0021] Furthermore, in addition to indicating location or positional relationship, some of the aforementioned terms may also have other meanings. For example, the term "above" may also be used in some cases to indicate a certain dependency or connection relationship. Those skilled in the art can understand the specific meaning of these terms in this application based on the specific circumstances.
[0022] Furthermore, the terms "installation," "setup," "equipped with," "connection," and "linked" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral structure; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium, or an internal connection between two devices, components, or parts. Those skilled in the art can understand the specific meaning of these terms in this application based on the specific circumstances.
[0023] Furthermore, the terms "first," "second," etc., are primarily used to distinguish different devices, components, or parts (which may be the same or different in specific type and construction), and are not intended to indicate or imply the relative importance or quantity of the indicated devices, components, or parts. Unless otherwise stated, "a plurality of" means two or more.
[0024] The technical solution of this application will be further described below with reference to the embodiments and accompanying drawings.
[0025] In perovskite solar cell technology, C 60 Due to its high electron mobility, excellent interface passivation ability, good film density, and low-temperature fabrication capability, perovskite has become a highly advantageous electron transport layer material in perovskite solar cells. However, the C0 of existing perovskite solar cells... 60 The perovskite layer contains highly enriched interface defects: numerous molecular dangling bonds and unsaturated coordination sites, resulting in poor microstructural stability and high sensitivity to environmental factors such as temperature, humidity, and continuous light exposure. This easily leads to interface aging and degradation, and induces the migration of active ions such as iodine ions in the perovskite layer, accelerating device degradation. Furthermore, the perovskite layer and C... 60 Poor energy level matching and the formation of a significant charge transport barrier at the interface severely hinder the efficient separation and extraction of photogenerated carriers, exacerbating nonradiative recombination losses. Ultimately, this leads to a significant decrease in the device fill factor and photoelectric conversion efficiency, limiting the device's long-term operational stability. Existing technologies often involve... (The sentence is incomplete and requires further context to be translated accurately.) 60 Organic small molecule materials such as organic ammonium salts (e.g., PEAI) are introduced as passivation layers to reduce interface defects. However, traditional single-molecule passivation materials have a single mechanism of action, only able to passivate some surface defects superficially, and cannot simultaneously achieve interface energy level optimization and effective isolation from environmental erosion; at the same time, their passivation layer coverage is uneven and their own stability is poor, making it difficult to specifically address the differences between perovskite and C-based materials. 60Multiple problems exist at the interface between the electron transport layers of the material, resulting in limited modification effects.
[0026] In view of this, firstly, this application provides a perovskite solar cell. For example... Figure 1 As shown, the perovskite solar cell includes a substrate 1 and a hole transport layer 2, a perovskite layer 3, a composite passivation layer 4, and an electron transport layer 5 sequentially stacked on the substrate 1. (Reference) Figure 2 The composite passivation layer 4 comprises a stacked first passivation sublayer 41, a second passivation sublayer 42, and a third passivation sublayer 43. The first passivation sublayer 41 is in contact with the perovskite layer 3, and the third passivation sublayer 43 is in contact with the electron transport layer 5. The first passivation sublayer 41 contains an ionic compound with a molecular weight not exceeding 300, which is a class of small molecule ionic compounds. The ionic compound contains at least one of amino, amidine, fluorine, and thiocyanate groups. The second passivation sublayer 42 contains an organic iodide. The third passivation sublayer 43 contains an n-type electron acceptor material.
[0027] The perovskite solar cell provided in this application includes a composite passivation layer comprising a stacked first passivation sublayer, a second passivation sublayer, and a third passivation sublayer. The first passivation sublayer contains at least one of amino, amidine, fluorine, and thiocyanate groups. It has a small molecular size and strong penetration ability, enabling it to penetrate deep into the grain boundaries of the perovskite layer and reconstruct the interface between the perovskite layer and the electron transport layer. It can also passivate uncoordinated Pb in the perovskite layer. 2+ And halogen defects; the second passivation sublayer contains a second passivation material, which is an organic iodide, capable of inducing band bending to achieve field-effect passivation, while forming a dense physical barrier, which can not only inhibit the ion migration of perovskite material in the perovskite layer, but also block water and oxygen from intruding into the perovskite layer; the third passivation sublayer contains a third passivation material, which is an n-type electron acceptor material. On the one hand, it can form specific interactions such as hydrogen bonds, electrostatic interactions and coordination bonds with the Ruddlesden-Popper (RP) two-dimensional phase surface of the second sublayer. On the other hand, the third passivation sublayer is an ordered two-dimensional functional layer, which can precisely regulate the dipole and energy level alignment of the interface between the perovskite layer and the electron transport layer, strengthen the hydrophobic barrier ability of the interface, optimize the electron extraction kinetics, that is, the process of electrons crossing the interface barrier between the perovskite and the electron transport layer to inject into the electron transport layer; and it can also stabilize the multi-layer interface structure of the composite passivation layer and inhibit ion migration and environment-induced interface degradation. This application achieves a synergistic improvement in interfacial charge transport and long-term stability of perovskite tandem solar cells through the unique three-layer structure of the composite passivation layer and the synergistic effect of the materials.
[0028] In summary, at the interface between the perovskite layer and the electron transport layer, especially the perovskite / C layer... 60This application constructs a sandwich-style multi-level passivation structure to simultaneously achieve defect passivation, energy level modulation, and environmental shielding, systematically optimizing the performance of tandem devices. The first layer introduces an ultrathin small-molecule passivation layer (i.e., the first passivation sublayer). Leveraging its small molecular size, multi-functional group synergy, and strong penetration ability, it penetrates deep into the grain boundaries to complete interface reconstruction, effectively passivating various types of intrinsic defects, improving local conductivity, and suppressing non-radiative recombination. The second passivation sublayer, located in the middle, serves as the structural main body, constructing a quasi-two-dimensional Ruddlesden-Popper phase. Through dual-cation-induced band bending, it achieves field-effect passivation while simultaneously constructing a dense physical barrier, significantly suppressing ion migration and water-oxygen erosion. The third passivation sublayer, located at the top, interacts specifically with the surface of the second passivation sublayer, further optimizing interface energy level matching, enhancing hydrophobic properties, and improving electron extraction capability. This three-level linkage strategy of point repair, surface protection, and interface modulation achieves comprehensive optimization from microscopic defect treatment to macroscopic stability improvement, providing an excellent interface technology solution for high-efficiency, high-stability, wide-bandgap perovskite / crystalline silicon tandem solar cells.
[0029] In one alternative implementation, refer to Figure 2 The thickness of the first passivation sublayer 41 is less than the thickness of the second passivation sublayer 42, and the thickness of the third passivation sublayer 43 is less than the thickness of the second passivation sublayer 42. That is, the second passivation sublayer 42 is thicker than the first passivation sublayer 41 and the third passivation sublayer 43. In this way, a dense and sufficiently thick physical barrier can be formed, which is more conducive to inhibiting the ion migration of perovskite material in the perovskite layer 3, and can also prevent water and oxygen from penetrating the perovskite layer 3.
[0030] In one alternative embodiment, the thickness of the first passivation sublayer 41 is 0.4 nm to 1.5 nm. For example, the thickness is 0.4 nm, 0.5 nm, 0.8 nm, 1 nm, 1.2 nm, 1.4 nm, or 1.5 nm. A thickness within the above range is beneficial for forming an ultrathin small-molecule passivation sublayer and facilitates the penetration of ionic compounds into the grain boundaries of the perovskite layer for passivation.
[0031] In one optional embodiment, the thickness of the second passivation sublayer 42 is 2 nm to 2.6 nm. For example, the thickness is 2 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.5 nm, or 2.6 nm. A thickness within the above range is beneficial for forming a dense and sufficiently thick physical barrier, which can not only inhibit ion migration of the perovskite material in the perovskite layer but also prevent water and oxygen from penetrating the perovskite layer.
[0032] In one optional embodiment, the thickness of the third passivation sublayer 43 is 0.6 nm to 1.5 nm. For example, the thickness is 0.6 nm, 0.7 nm, 0.8 nm, 1 nm, 1.2 nm, 1.4 nm, or 1.5 nm. A thickness within the above range is beneficial for enhancing the hydrophobic barrier ability of the interface between the perovskite layer and the electron transport layer, stabilizing the multilayer interface structure of the composite passivation layer, and suppressing ion migration and environment-induced interface degradation.
[0033] In one alternative embodiment, the ionic compound is selected from at least one of 1-[4-(trifluoromethyl)phenyl]biguanide hydrochloride, 1-phenylbiguanide hydrochloride, 4-(trifluoromethyl)benzamidinium hydrochloride, ammonium thiocyanate, and 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride. Preferably, 1-[4-(trifluoromethyl)phenyl]biguanide hydrochloride has a smaller molecular size, enabling it to penetrate the perovskite layer more effectively and reconstruct grain boundaries. This allows for deeper reconstruction of the interface between the perovskite layer and the electron transport layer, repairing various defects and thereby improving local conductivity and passivating defect sites.
[0034] In one optional embodiment, the organic iodide is selected from at least one of 1,3-diaminopropane dihydroiodide (PDAI2), ethylenediamine dihydroiodide (EDAI), malondiamidinium diiodide (PDI), 2-(4-fluorophenyl)ethylamine hydroiodide (pF-PEAI), straight-chain alkyl diammonium iodide, alicyclic diammonium iodide, aromatic diammonium iodide, fluorodiammonium hydroiodide, amidine iodide, and monocationic aralkylammonium iodide, wherein 1,3-diaminopropane dihydroiodide (PDAI2), ethylenediamine dihydroiodide (EDAI), malondiamidinium diiodide (PDI), and 2-(4-fluorophenyl)ethylamine hydroiodide (pF-PEAI) belong to organic hydroiodides.
[0035] In one alternative embodiment, the linear alkyl diammonium iodide is selected from at least one of 1,4-butanediammonium dihydroiodate (BDAI), 1,3-propanediammonium dihydroiodate (PeDAI), and 1,6-hexammonium dihydroiodate (HDAI). The alicyclic diammonium iodide is selected from at least one of 1,2-cyclohexanediammonium dihydroiodate (CyHDAI) and piperazine diammonium dihydroiodate (PipDAI); The aromatic diammonium iodide is selected from at least one of o-phenyl diammonium dihydroiodate (o-PDAI) and biphenyl diammonium dihydroiodate (BPDI); Fluorinated diammonium hydroiodates are selected from at least one of tetrafluoroethylenediammonium dihydroiodate (TFEDAI) and tetrafluorophenyldiammonium dihydroiodate (TFPDAI); The amidine iodides are selected from benzamide iodide (PDI2); The monocationic aralkylammonium iodide is selected from at least one of phenylethylammonium iodide (PEAI) and fluorophenylethylammonium iodide (FPEAI).
[0036] Preferably, PEAI contains a monovalent phenylethylammonium cation, which can in-situ construct a Ruddlesden–Popper (RP) two-dimensional perovskite passivation layer on the perovskite layer surface; EDAI2 and PDAI2 are divalent diammonium cations with protonated amino groups at both ends, which can in-situ construct a Dion-Jacobson (DJ) two-dimensional perovskite on the perovskite layer surface. PEAI, EDAI2, and PDAI2 can all more effectively passivate lead-related defects on the perovskite surface, improve the hydrophobicity of the film, construct an interface dipole-optimized energy level matching, and reduce interfacial nonradiative recombination.
[0037] In one optional embodiment, the n-type electron acceptor material is selected from at least one of p-trifluoromethylbenzonitrile (TFBN), p-fluorobenzonitrile (FBN), and pentafluorobenzoic acid (PFBA). These materials possess a conjugated / large π-electron system and further have strong electron-withdrawing groups, such as fluorine (-F), cyano (-CN), or carbonyl (-COOH), which are more conducive to the formation of an ordered two-dimensional functional layer. TFBN is preferred as the n-type electron acceptor material.
[0038] In one alternative embodiment, the material of the electron transport layer may include C 60 Fullerene C 70 At least one of (6,6)-phenyl-C61-butyrate methyl ester (PCBM) and 4-(1',5'-dihydro-1'-methyl-2'H-(5,6)fullerene-C60-In-(1,9-c)pyrrole-2'-yl)benzamine chloride (CPMAC).
[0039] In one alternative implementation, refer to Figure 3 The substrate 1 includes a bottom cell 10 and a composite layer 17 disposed on the bottom cell 10. The composite layer 17 is disposed between the bottom cell 10 and the hole transport layer 2. In this case, the perovskite solar cell is a perovskite tandem solar cell. The hole transport layer 2, the perovskite layer 3, the composite passivation layer 4, and the electron transport layer 5 constitute the top cell of the perovskite tandem solar cell.
[0040] When the substrate 1 includes a bottom cell 10 and a composite layer 17, the first transparent electrode layer 7 is located on the front side of the perovskite tandem solar cell. A buffer layer 6, the first transparent electrode layer 7, a positive electrode 91, and an anti-reflection layer 8 are further stacked on the side of the electron transport layer 5 away from the perovskite layer 3. A back electrode 92 is disposed on the side of the bottom cell 10 away from the composite layer 17. The positive electrode 91 uses electrode grid lines, and the anti-reflection layer 8 covers the electrode grid lines and the areas of the first transparent electrode layer 7 not covered by the electrode grid lines. In this way, the first transparent electrode layer 7 collects photogenerated electrons exported from the electron transport layer 6 and transports them to the electrode grid lines, while also reducing the reflection of incident light on the surface of the perovskite solar cell and increasing the absorption of light by the perovskite solar cell. The electrode grid lines efficiently collect and export the electrons transported by the first transparent electrode layer 7. The patterned electrode grid lines reduce shading losses while ensuring conductivity, thus improving the photoelectric conversion efficiency of the perovskite solar cell. The first transparent electrode layer 7 and the electrode grid lines together constitute a high-efficiency current collection and export system for the perovskite solar cell.
[0041] The electrode grid line material includes at least one of gold (Au), silver (Ag), aluminum (Al) and copper (Cu); preferably silver, copper or aluminum.
[0042] Furthermore, the thickness of the electrode grid lines can be 0.3 μm to 20 μm.
[0043] Furthermore, the electrode grid lines include fine grids and busbar grids. Multiple fine grids are arranged in parallel on the first transparent electrode layer 7 to collect photogenerated electrons exported from the electron transport layer. The busbar grids are in contact with the fine grids to collect all the current transmitted through the fine grids and output it outward. The thickness of the fine grids is 5μm~15μm, and the width is 20μm~50μm. The thickness of the busbar grids is 1.5μm~2μm, and the width is 1.2μm~2mm.
[0044] Furthermore, an adhesion layer can be disposed between the electrode grid lines and the first transparent electrode layer 7. This adhesion layer binds the electrode grid lines to the first transparent electrode layer 7, preventing metal atoms in the electrode grid lines from extending into the first transparent electrode layer 7 and reducing the interfacial contact barrier. The adhesion layer is made of at least one of chromium (Cr), titanium (Ti), nickel (Ni), platinum (Pt), and palladium (Pd). The thickness of the adhesion layer is 5 nm to 20 nm.
[0045] Furthermore, the bottom cell 10 is selected from crystalline silicon bottom cells, copper inert gallium selenide (CIGS) thin-film bottom cells, cadmium telluride thin-film bottom cells, III-V thin-film bottom cells, or perovskite bottom cells. Among them, crystalline silicon bottom cells include at least one of heterojunction (HJT) cells, tunnel oxide passivated contact (TOPCon) cells, and passivated emitter and back contact (PERC) cells.
[0046] The composite layer 17 can be made of a transparent conductive oxide, including at least one of indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), indium zirconium oxide (IZrO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), antimony-doped tin oxide (ATO), and gallium-doped zinc oxide (GZO). The transparent conductive oxide can be prepared by methods including, but not limited to, magnetron sputtering (PVD) and reactive plasma deposition (RPD).
[0047] Furthermore, the thickness of the transparent conductive oxide composite layer 17 is 2nm~20nm.
[0048] Furthermore, the material of the composite layer 17 can also be a tunneling junction, including an oxide tunneling junction or a silicon-based tunneling junction.
[0049] For example, the oxide tunneling junction can be NiO x / TiO x A double-layer oxide tunnel junction, wherein NiO x The thickness can be 2nm~10nm, TiO x The thickness can be 2nm to 10nm.
[0050] For example, a silicon-based tunneling junction can be n + -Si / p + -Si tunnel junction, where n + -The thickness of Si can be 2nm~15nm, p + The thickness of -Si can be 2nm~15nm.
[0051] Furthermore, the heterojunction cell comprises, from bottom to top, a second transparent electrode layer 11, a p-type window layer 12, a first intrinsic hydrogenated amorphous silicon passivation layer 13, an n-type silicon substrate 14, a second intrinsic hydrogenated amorphous silicon passivation layer 15, and an n-type window layer 16. A composite layer 17 is disposed between the n-type window layer 16 and the hole transport layer 2, and a back electrode 92 is disposed on the side of the second transparent electrode layer 11 away from the p-type window layer 12.
[0052] The material of the second transparent electrode layer 11 includes, but is not limited to, indium tin oxide (ITO), indium zinc oxide (IZO), indium tungsten oxide (IWO), indium zirconium oxide (IZrO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), antimony-doped tin oxide (ATO), and gallium-doped zinc oxide (GZO). The preparation method includes, but is not limited to, magnetron sputtering (PVD) and reactive plasma deposition (RPD). The thickness of the second transparent electrode layer 11 can be 20 nm to 100 nm.
[0053] The materials of the p-type window layer 12 include: p-type hydrogenated nanocrystalline silicon (p-nc-Si:H) and p-type hydrogenated nanocrystalline silicon oxide (p-nc-SiO). x p-type hydrogenated amorphous silicon (pa-Si:H), p-type hydrogenated nanocrystalline silicon-carbon (p-nc-SiC:H), p-type hydrogenated amorphous silicon-oxygen (pa-SiO) x At least one of p-type hydrogenated nanocrystalline silicon (p-nc-Si:H) or p-type hydrogenated nanocrystalline silicon oxide (p-nc-SiO) is preferred. x :H).
[0054] The materials of the n-type window layer 16 include: n-type hydrogenated nanocrystalline silicon (n-nc-Si:H) and n-type hydrogenated nanocrystalline silicon oxide (n-nc-SiO). x n-type hydrogenated amorphous silicon (na-Si:H), n-type hydrogenated amorphous silicon oxide (na-SiO) x At least one of n-type hydrogenated amorphous silicon-carbon (na-SiC:H) and n-type hydrogenated nanocrystalline silicon (n-nc-Si:H) or n-type hydrogenated nanocrystalline silicon-oxygen (n-nc-SiO) is preferred. x :H).
[0055] It is understandable that the back electrode 92 can cover the entire back of the bottom cell 10 in a patterned manner; when the back electrode 92 is patterned, it forms an electrode grid line; when the back electrode 92 covers the entire back, it is a continuous back electrode. The second transparent electrode layer 11 is a continuous full-coverage thin film, which can collect holes exported from the p-type window layer 12 over the entire area, shortening the lateral transmission distance of holes in the p-type window layer 12, thereby reducing the overall lateral transmission loss in the p-type window layer 12. The back electrode 92 efficiently collects holes exported from the p-type window layer 12 and reflects unused long-wavelength photons back into the perovskite solar cell for secondary absorption.
[0056] Furthermore, the material of the back electrode 92 includes at least one of aluminum (Al), copper (Cu), silver (Ag), gold (Au), and silver-clad copper, wherein aluminum is suitable for the back electrode 92 that fully covers the p-type window layer 12, and silver, copper, and silver-clad copper are suitable for the back electrode 92 that patternedly covers the p-type window layer 12.
[0057] An adhesion layer may also be disposed between the back electrode 92 and the p-type window layer 12. This adhesion layer serves to adhere the back electrode 92 to the p-type window layer 12 and also prevents metal atoms in the back electrode 92 from diffusing into the p-type window layer 12. The material of the adhesion layer includes at least one of titanium (Ti), chromium (Cr), nickel (Ni), and cobalt (Co), preferably titanium, chromium, or a composite structure of titanium and chromium. The thickness of the adhesion layer is 5 nm to 20 nm.
[0058] The hole transport layer 2 is made of at least one of self-assembled monolayer materials, transition metal oxide materials, and inorganic materials. The material of the hole transport layer 2 can be a single material selected from self-assembled monolayer materials, transition metal oxide materials, and inorganic materials, or it can be a combination of multiple materials.
[0059] For example, refer to Figure 3 The hole transport layer 2 comprises a stacked transition metal oxide layer 21 and a self-assembled monolayer 22. The transition metal oxide layer material includes at least one of nickel oxide, copper oxide, cobalt tetroxide, and ferric oxide. The preparation processes for the transition metal oxide material include solution methods, physical vapor deposition (PVD), atomic layer deposition (ALD), and inkjet printing.
[0060] Self-Assembled Monolayer (SAM) materials are generally composed of anchoring groups, alkyl bridges, and terminal groups.
[0061] The anchoring group contains polar atoms such as oxygen, phosphorus, and sulfur, existing as active functional groups such as phosphonic acid groups (-PO(OH)2), carboxyl groups (-COOH), hydroxyl groups (-OH), and thiol groups (-SH). The terminal groups include carbazole groups, dibenzocarbazole groups, acridine groups, phenothiazine groups, or phenyl groups. These terminal groups have a conjugated structure, and their π-electron clouds can compensate for the charge of halogen vacancies in the perovskite layer, thereby filling the shallow energy level defects caused by halogen vacancies. Among these, the nitrogen atoms in nitrogen-containing terminal groups such as carbazole, dibenzocarbazole, acridine, and phenothiazine contain lone pairs of electrons, which can interact with uncoordinated divalent cations (such as lead ions Pb) on the perovskite layer surface. 2+ This forms coordination bonds, thereby precisely passivating deep-level defects caused by uncoordinated divalent cations.
[0062] Substituents can be further introduced onto the terminal group. These substituents can regulate the electron cloud density of the terminal group, enhancing its coordination strength with uncoordinated divalent cations and improving defect passivation efficiency. Simultaneously, the substituents can form coordination bonds with uncoordinated divalent cations on the perovskite layer surface, or occupy halogen vacancies through their own electronegativity and lone pair electrons, achieving charge compensation and space filling at defect sites, thereby effectively suppressing grain boundary defects. Exemplarily, the substituents include at least one of halogen substituents, alkyl groups, alkoxy groups, benzene substituents, and bis(4-methoxyphenyl)amino groups.
[0063] Alkyl bridges are the "backbone" connecting anchor groups and terminal groups, and are typically composed of saturated carbon chains. The length of an alkyl bridge directly determines the spatial distance between the anchor group and the terminal group, and its chain length and chemical properties further affect the molecular order, conductivity, and steric hindrance of self-assembled monolayer materials.
[0064] A transition metal oxide layer 21 is disposed between the composite layer 17 and the self-assembled monolayer 22. The surface of the transition metal oxide layer 21 is rich in hydroxyl groups. The anchoring groups of SAM form covalent or coordinate bonds with the metal ions and hydroxyl groups on the surface of the transition metal oxide, promoting the dense and uniform growth of the SAM material into a film. The terminal groups of SAM can compensate for the charge of halogen vacancies in the perovskite layer by means of the conjugated π electron cloud, and can also form coordinate bonds with uncoordinated divalent cations on the perovskite surface, achieving dual passivation of interface defects. At the same time, the interface energy level arrangement is precisely controlled to reduce the hole extraction barrier and effectively suppress non-radiative recombination at the interface.
[0065] Self-assembled monolayer (SAM) materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz, CAS No. 20999-38-6), [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-2PACz, CAS No. 2996161-30-7), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz, CAS No. 2377770-18-6), and [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Ph-2PACz, CAS No. 3085827-62-6). [2-(3,6-Diiodo-9H-carbazole-9-yl)ethyl]phosphonic acid (I-2PACz, CAS No. 3026275-69-1), [2-(3,6-dibromo-9H-carbazole-9-yl)ethyl]phosphonic acid (Br-2PACz, CAS No. 2762888-11-7), [2-(3,6-dichloro-9H-carbazole-9-yl)ethyl]phosphonic acid (Cl-2PACz, CAS No. 3036926-72-1), [2-(3,6-difluoro-9H-carbazole-9-yl)ethyl]phosphonic acid (F-2PACz, CAS No. 3036926-69-6), [2-(7H-dibenzocarbazole) [2-(9H-9'-phenyl-3,3'-dicarbazole-9-yl)ethyl]phosphoric acid (2PADCB, CAS No. 2882156-61-6), [2-(9H-9'-phenyl-3,3'-dicarbazole-9-yl)ethyl]phosphoric acid (2PABCz), [4-(9H-carbazole-9-yl)butyl]phosphoric acid (4PACz, CAS No. 20999-36-4), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz, CAS No. 2747959-96-0), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz, CAS No. 2922526-5) 6-3), [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphoric acid (Ph-4PACz, CAS No. 2814500-04-2), [4-(3,6-diiodo-9H-carbazole-9-yl)butyl]phosphonic acid (I-4PACz, CAS No. 3026275-67-9), [4-(3,6-dibromo-9H-carbazole-9-yl)butyl]phosphonic acid (Br-4PACz, CAS No. 2996161-28-3), [4-(3,6-dichloro-9H-carbazole-9-yl)butyl]phosphonic acid (Cl-4PACz, CAS No. 3026275-66-8), [4-(3,[6-Difluoro-9H-carbazole-9-yl)butyl]phosphonic acid (F-4PACz, CAS No. 3026275-65-7), [4-[3-bromo-6-(4-methoxyphenyl)-9H-carbazole-9-yl]butyl]phosphonic acid (BrMeOPh-4PACz, CAS No. 3053380-37-0), [4-(3,6-di-tert-butyl-9H-carbazole-9-yl)butyl]phosphonic acid (tBu-4PACz, CAS No. 3023627-39-3), [4-(7H-dibenzo-carbazole-7-yl)butyl]phosphonic acid (4PADCB, CAS No. 2882156-63-8), [4-(9H-9` [Phenylacetic-3,3'-dicarbazole-9-yl)butyl]phosphoric acid (4PABCz), [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]phosphonic acid (2Br-4DMAcPA / DMAcPA, CAS No. 2971088-37-4), [2-(3,7-dibromo-10H-phenthiazin-10-yl)ethyl]phosphonic acid (Br-2EPT, CAS No. 2826271-17-2), and [2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl]phosphonic acid (MPA-CPA, CAS No. 2212003-31-9)]phosphonic acid.
[0066] Furthermore, the thickness of the self-assembled monolayer 22 can be 0.5 nm to 5 nm. The thickness of the transition metal oxide layer 21 can be 5 nm to 30 nm.
[0067] The hole transport layer, perovskite layer, composite passivation layer, and electron transport layer of this application can also be applied to single-junction perovskite solar cells. Single-junction perovskite solar cells include rigid single-junction perovskite solar cells and flexible single-junction perovskite solar cells.
[0068] Secondly, this application provides a method for fabricating a perovskite solar cell as described in the first aspect, comprising the following steps: Step A: Provide a substrate, which includes a bottom cell and a composite layer; Step B: Sequentially prepare a hole transport layer and a perovskite layer on the surface of the composite layer; Step C: Sequentially prepare a first passivation sublayer, a second passivation sublayer, and a third passivation sublayer on the surface of the perovskite layer to form a composite passivation layer; Step D: Sequentially prepare other functional layers on the surface of the composite passivation layer, including at least an electron transport layer.
[0069] In step C, the preparation method of the first passivation sublayer includes: mixing a first passivating material with a solvent to obtain a first passivation solution, wherein the concentration of the first passivating material in the first passivation solution is 0.3 mg / mL to 1 mg / mL; coating the first passivation solution onto the surface of the perovskite layer; and annealing at 80℃ to 120℃ for 5 min to 30 min to obtain an ultrathin small molecule passivation layer, i.e., the first passivation sublayer. The first passivation layer is very thin and is not easily observed under a scanning electron microscope (SEM), but a frosted surface can be seen.
[0070] The method for preparing the second passivation sublayer includes: mixing a second passivating material with a solvent to obtain a second passivation solution, wherein the concentration of the second passivating material in the second passivation solution is 0.3 mg / mL to 1 mg / mL; coating the second passivation solution onto the surface of the first passivation sublayer; and annealing at 80℃ to 120℃ for 5 min to 30 min to obtain the second passivation sublayer. Because the first passivation sublayer is anchored to the perovskite layer, when the second passivation sublayer is coated, the small molecule ionic compounds that have already participated in the passivation coordination reaction will not be dissolved; only some of the unreacted small molecule ionic compounds will dissolve.
[0071] The preparation method of the third passivation sublayer includes: mixing the third passivation material with a solvent to obtain the third passivation solution, wherein the concentration of the third passivation material in the passivation solution is 0.3 mg / mL to 1 mg / mL; coating the third passivation solution onto the surface of the second passivation sublayer; and annealing at 80℃ to 120℃ for 5 min to 30 min to obtain the third passivation sublayer.
[0072] This application does not impose any particular limitation on the solvents in the first, second, and third passivation solutions, as long as they can dissolve the corresponding passivation material. For example, they may include, but are not limited to, isopropanol and chlorobenzene. This application can form the first, second, and third passivation sublayer wet films through spin coating and immersion processes.
[0073] This application provides a method for fabricating a perovskite solar cell, which involves sequentially fabricating a first passivation sublayer, a second passivation sublayer, and a third passivation sublayer on the surface of a perovskite layer, thereby forming a composite passivation layer with a three-layer composite structure. The fabrication process of this application is simple and convenient to operate, requiring no major modifications to the existing fabrication process of tandem perovskite solar cells, which is beneficial for industrial production and suitable for large-scale manufacturing of perovskite-silicon tandem solar cells.
[0074] Thirdly, this application provides a photovoltaic module comprising: at least one cell string, the cell string comprising at least two perovskite solar cells as described in any of the above embodiments.
[0075] Example The perovskite solar cells, their fabrication methods, and photovoltaic modules of this application will be further described below with reference to more specific embodiments.
[0076] Example 1 <Clean Silicon Base Battery> The crystalline silicon base cell comprises an n-type monocrystalline silicon substrate with a length of 210 mm, a width of 105 mm, and a thickness of 100 μm. A 10 nm thick p-type hydrogenated nanocrystalline silicon window layer (i.e., a p-type window layer) is sequentially deposited on the back side of the n-type monocrystalline silicon substrate. A 20 nm thick indium tin oxide (ITO) second transparent electrode layer and a 5 μm thick silver electrode grid line are then sequentially deposited on the front side of the n-type monocrystalline silicon substrate. An n-type hydrogenated nanocrystalline silicon window layer (i.e., an n-type window layer) and a 10 nm thick indium tin oxide (ITO) composite layer are then sequentially deposited on the front side of the n-type monocrystalline silicon substrate. Using a spin coater, ethanol is spin-coated onto the indium tin oxide (ITO) composite layer on the front side of the crystalline silicon base cell at a speed of 3000 rpm for 30 s, repeated twice. The surface is then heat-treated at 200 °C for 10 min to complete the cleaning process.
[0077] <Preparation of Hole Transport Layer> The crystalline silicon bottom cell is placed in a sputtered nickel oxide (NiO) layer. x The mask is placed in a magnetron sputtering apparatus and a vacuum of 7 × 10⁻⁶ is drawn. -4 Below Pa, select the radio frequency magnetron sputtering mode, adjust the power to 200W, set the argon flow rate to 30sccm, and sputter for 1 min 50 s to form a 15 nm thick nickel oxide (NiO) layer on the indium tin oxide (ITO) composite layer. x The self-assembled monolayer material [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid (4PADCB) was mixed with anhydrous ethanol and stirred until completely dissolved to obtain a self-assembled monolayer (SAM) solution with a concentration of 1 mg / mL. The SAM solution was spin-coated onto a nickel oxide layer at a spin speed of 3000 rpm for 30 s. Then, it was heated and annealed on a hot plate at 100 °C for 10 min to form a self-assembled monolayer (SAM) with a thickness of 2.2 nm. The nickel oxide layer and the self-assembled monolayer constitute a hole transport layer.
[0078] <Preparation of Perovskite Layer> In a glove box under a nitrogen atmosphere, perovskite precursor materials CsI, PbI2, FABr, and methylammonium iodide (MAI) were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (volume ratio 4:1). The solution was stirred at room temperature until completely dissolved to obtain a perovskite precursor solution; wherein, the A-site cation CsI... + FA +MA + The total molar concentration is 1 mol / L, and the atomic ratio of Cs, FA, and MA is 0.05:0.75:0.2. The B-site cation is Pb. 2+ The molar concentration is 1 mol / L.
[0079] In a glove box under a nitrogen atmosphere, a perovskite precursor solution was coated onto the hole transport layer using a slot coating process to form a wet perovskite precursor film. The process parameters for slot coating were: slot solution extrusion speed of 10 m / min. - ¹, Coating blade moving speed 10 mm·s - ¹, the crystalline silicon bottom cell supporting the wet perovskite precursor film was transferred to a vacuum crystallization and drying apparatus and kept under a vacuum of 10 Pa for 120 s to obtain a dry perovskite precursor film; subsequently, the crystalline silicon bottom cell supporting the dry perovskite precursor film was transferred to a hot stage at 100 °C and heated and annealed for 30 min to form a silicon cell with the chemical formula Cs. 0.05 FA 0.75 MA 0.2 Pb(I) 0.75 Br 0.25 3. A perovskite layer with a thickness of 250 nm.
[0080] <Preparation of Composite Passivation Layer> <Preparation of the first passivation sublayer> The first passivation material, 1-[4-(trifluoromethyl)phenyl]biguanidine hydrochloride, was mixed with isopropanol to obtain the first passivation solution. The concentration of 1-[4-(trifluoromethyl)phenyl]biguanidine hydrochloride in the first passivation solution was 1 mg / mL. The first passivation solution was coated on the surface of the perovskite layer using a slit coating process and annealed at 80°C for 5 min to obtain a first passivation sublayer with a thickness of 1.5 nm.
[0081] <Preparation of the second passivation sublayer> The second passivation material, 1,3-diaminopropane dihydroiodate (PDAI2, CAS No.: 120675-53-8), was mixed with isopropanol to obtain a second passivation solution. The concentration of PDAI2 in the second passivation solution was 1 mg / mL. The second passivation solution was coated onto the surface of the first passivation sublayer using a slit coating process. The solution was then annealed at 100°C for 5 min to obtain a second passivation sublayer with a thickness of 2 nm.
[0082] <Preparation of the third passivation sublayer> The third passivation material, p-fluorobenzonitrile (FBN), was mixed with isopropanol to obtain a third passivation solution. The concentration of FBN in the third passivation solution was 1 mg / mL. The third passivation solution was coated onto the surface of the second passivation sublayer using a slit coating process. After annealing at 100°C for 5 min, a third passivation sublayer with a thickness of 1.5 nm was obtained, forming a composite passivation layer.
[0083] <Preparation of Electron Transport Layer> A 20nm thick C layer was deposited on the third passivation sublayer using a vacuum evaporation process. 60 Electron transport layer, deposition rate 0.5 Å / s.
[0084] <Preparing a buffer layer> Atomic layer deposition (ALD) was used in C 60 Tin oxide (SnO) with a thickness of 10 nm was prepared on the electron transport layer. x ) Buffer layer.
[0085] <Preparation of the first transparent electrode layer> Using radio frequency magnetron sputtering technology, tin oxide (SnO) is sputtered. x A first transparent electrode layer of indium zinc oxide (IZO) with a thickness of 100 nm was deposited on the buffer layer. The sputtering power was controlled at 300 W, the chamber pressure at 0.6 Pa, the argon flow rate at 20 sccm, the 5% argon-oxygen mixed flow rate at 5 sccm, and the sputtering time at 100 s.
[0086] <Preparation of Silver Electrode Grid Lines> Using screen printing, a silver fine grid with a thickness of 8 μm and a width of 50 μm and a silver busbar with a thickness of 1.5 μm and a width of 1.5 mm are prepared on an indium zinc oxide (IZO) transparent electrode layer. The fine grid and the busbar constitute the silver electrode grid lines.
[0087] <Preparation of Antireflective Layer> A 100 nm thick lithium fluoride antireflection layer was deposited on the silver electrode grid lines and the first transparent electrode layer not covered by the silver electrode grid lines using a vacuum evaporation process to obtain a perovskite / crystalline silicon tandem solar cell with an evaporation rate of 1 Å / s.
[0088] Examples 2 to 4 Except for adjusting the thicknesses of the first passivation sublayer, the second passivation sublayer, and the third passivation sublayer according to Table 1 in the <Preparation of Composite Passivation Layer> section, the rest is the same as in Example 1.
[0089] Examples 5 to 14 Except for adjusting the materials of the first passivation sublayer, the second passivation sublayer, and the third passivation sublayer according to Table 1 in the <Preparation of Composite Passivation Layer> section, the rest is the same as in Example 1.
[0090] Comparative Example 1 Except for the use of a single-layer passivation layer, the process is the same as in Example 1. The preparation steps of the single-layer passivation layer are as follows: The passivating material PDAI2 was mixed with isopropanol to obtain a passivation solution with a PDAI2 concentration of 1 mg / mL. The passivation solution was coated onto the surface of the perovskite layer and annealed at 65 °C for 5 min to obtain a passivation layer with a thickness of 2 nm.
[0091] Comparative Example 2 Compared to Example 1, the step of preparing the third passivation sublayer is omitted. Instead, after preparing the second passivation sublayer, a 20 nm thick C layer is directly deposited on the second passivation sublayer. 60 The electron transport layer operates the same as in Example 1.
[0092] Comparative Example 3 Compared to Example 1, the operation of preparing the second passivation sublayer is omitted. After preparing the first passivation sublayer, the third passivation sublayer is prepared directly on the first passivation sublayer. Other operations are the same as in Example 1.
[0093] Comparative Example 4 Compared to Example 1, the preparation of the first passivation sublayer is omitted. Instead, the second passivation sublayer is prepared directly on the perovskite layer after the perovskite layer is prepared. All other operations are the same as in Example 1.
[0094] Comparative Example 5 Compared to Example 1, the passivation layer operation is omitted, and C is directly prepared on the perovskite layer. 60 The electron transport layer operates the same as in Example 1.
[0095] Table 1: Preparation parameters for each example and comparative example
[0096] In Table 1, " / " indicates that no relevant preparation parameters exist.
[0097] Performance testing: Open-circuit voltage, short-circuit current density, and fill factor tests: The current (I)-voltage (V) of the solar cells in each embodiment and comparative example were measured using an IV tester (model: VS-6831S, manufacturer: Suzhou Weixin Intelligent Technology Co., Ltd.) to obtain the open-circuit voltage, short-circuit current density, fill factor and photoelectric conversion efficiency of the solar cells.
[0098] Table 2: Performance data of each embodiment and comparative example
[0099] As can be seen from Examples 1-14 and Comparative Examples 1-5, the photoelectric conversion efficiency of Comparative Examples 1-5 is relatively low. This may be because Comparative Example 1 uses a traditional single-layer passivation layer structure, which is difficult to completely eliminate the interface defects between the perovskite layer and the electron transport layer; Comparative Examples 2 to 4 only use part of the passivation sublayer in the three-layer composite structure provided in this application, which has a limited effect on improving the efficiency of the perovskite solar cell; and Comparative Example 5 eliminates the passivation layer structure, making it difficult to eliminate the interface defects between the perovskite layer and the electron transport layer. In contrast, this application forms a composite passivation layer with a three-layer composite structure, which can further eliminate the interface defects between the perovskite layer and the electron transport layer, and significantly improve the open-circuit voltage and fill factor of the perovskite solar cell.
[0100] The above provides a detailed description of a perovskite solar cell, its preparation method, and photovoltaic module disclosed in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the technical solutions and core inventive points of the embodiments of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A perovskite solar cell, characterized in that, include: The substrate and the hole transport layer, perovskite layer, composite passivation layer and electron transport layer are sequentially stacked on the substrate; The composite passivation layer includes a first passivation sublayer, a second passivation sublayer, and a third passivation sublayer stacked together. The first passivation sublayer is in contact with the perovskite layer, and the third passivation sublayer is in contact with the electron transport layer. The first passivation sublayer contains a first passivation material, which is an ionic compound with a molecular weight of no more than 300, and the ionic compound contains at least one of amino, amidine, fluorine and thiocyanate groups. The second passivation sublayer contains a second passivation material, which is an organic iodide; The third passivation sublayer contains a third passivation material, which is an n-type electron acceptor material.
2. The perovskite solar cell according to claim 1, characterized in that, The thickness of the first passivation sublayer is less than the thickness of the second passivation sublayer, and the thickness of the third passivation sublayer is less than the thickness of the second passivation sublayer.
3. The perovskite solar cell according to claim 1, characterized in that, The composite passivation layer satisfies at least one of the following characteristics: a) The thickness of the first passivation sublayer is 0.4 nm to 1.5 nm; b) The thickness of the second passivation sublayer is 2 nm to 2.6 nm; c) The thickness of the third passivation sublayer is 0.6 nm to 1.5 nm.
4. The perovskite solar cell according to claim 1, characterized in that, The ionic compound is selected from at least one of 1-[4-(trifluoromethyl)phenyl]biguanide hydrochloride, 1-phenylbiguanide hydrochloride, 4-(trifluoromethyl)benzamidinium hydrochloride, ammonium thiocyanate and 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride.
5. The perovskite solar cell according to claim 1, characterized in that, The organic iodide is selected from at least one of 1,3-diaminopropane dihydroiodate, ethylenediamine dihydroiodate, malondiamidinium diiodate, 2-(4-fluorophenyl)ethylamine hydroiodate, straight-chain alkyl diammonium iodide, alicyclic diammonium iodide, aromatic diammonium iodide, fluorodiammonium hydroiodate, amidine iodide, and monocationic aralkylammonium iodide.
6. The perovskite solar cell according to claim 5, characterized in that, The straight-chain alkyl diammonium iodide is selected from at least one of 1,4-butanediammonium dihydroiodate, 1,3-propanediammonium dihydroiodate, and 1,6-hexammonium dihydroiodate; The alicyclic diammonium iodide is selected from at least one of 1,2-cyclohexanediammonium dihydroiodate and piperazine diammonium dihydroiodate; The aromatic diammonium iodide is selected from at least one of o-phenyl diammonium dihydroiodate and biphenyl diammonium dihydroiodate; The fluorodiammonium hydroiodate is selected from at least one of tetrafluoroethylenediammonium dihydroiodate and tetrafluorophenyldiammonium dihydroiodate; The amidine-based iodides are selected from benzamide iodides; The monocationic aralkylammonium iodide is selected from at least one of phenylethylammonium iodide and fluorophenylethylammonium iodide.
7. The perovskite solar cell according to claim 1, characterized in that, The n-type electron acceptor material is selected from at least one of p-trifluoromethylbenzonitrile, p-fluorobenzonitrile, and pentafluorobenzoic acid.
8. The perovskite solar cell according to claim 1, characterized in that, The material of the electron transport layer includes C. 60 Fullerene C 70 At least one of (6,6)-phenyl-C61-butyrate methyl ester and 4-(1',5'-dihydro-1'-methyl-2'H-(5,6)fullerene-C60-In-(1,9-c)pyrrole-2'-yl)benzamine chloride.
9. A method for preparing a perovskite solar cell according to any one of claims 1 to 8, characterized in that, Includes the following steps: A substrate is provided, the substrate comprising a bottom cell and a composite layer; A hole transport layer and a perovskite layer are sequentially prepared on the surface of the composite layer. The first passivation sublayer, the second passivation sublayer, and the third passivation sublayer are sequentially prepared on the surface of the perovskite layer to form the composite passivation layer; Other functional layers are sequentially prepared on the surface of the composite passivation layer, and the other functional layers include at least the electron transport layer.
10. A photovoltaic module, characterized in that, include: At least one battery string, the battery string comprising at least two perovskite solar cells as described in any one of claims 1 to 8.